STRES KERJA DENGAN KEJADIAN HIPERTENSI PADA PEDAGANG PASAR TRADISIONAL - I Made Sukarja (Jurnal Gema Keperawatan, 2019)
This study aimed to determine the relationship of work stress with the incidence of hypertension in traditional market traders in the work area of the Public Health Unit of Sukawati II in 2019. The type of research used is non-experimental with correlational types and cross sectional approaches using non probability sampling with purposive sampling. The sample is 161 people. Data collection method used was a work stress questionnaire and a sphygmanometer. The results showed that the majority of market traders were work stres 48,4 % and hypertension 68, 3 %.  Conclusion: there is a significant relationship between work stress and the incidence of hypertension in traditional market traders in the work area of the Sukawati II Public Health Unit in 2019 with p = 0,000 p α (0.05) and or14.211.